PENGARUH CITRA MEREK TERHADAP MINAT BELI : STUDI PADA PRODUK KECANTIKAN - Fauziah, Ninda; Aziz Mubarok, Dadan Abdul (IMAGE : Jurnal Riset Manajemen, 2019)
This study aims to analyze the impact of brand image on purchase intention of Safi Skincare in the city of Bandung. The research method approach uses a quantitative method. The research sample of 99 respondents. Data obtained by crossing the questionnaire. Data analysis using linear regression. Dimensions to measure the impact of brand image on consumer purchase intention by consumer perceptions, product brand slogans and brand positioning. The results of the study explain that brand image significantly influences purchase intention. The theoretical implication of this research is brand image influences purchase intention with a very strong (positive) relationship and is proportional. While the study's implications are aimed at the skincare cosmetics industry, it is expected to become one of the references in business management by optimizing brand utilization, because brand is one of the most influential things and can be used as a very promising and profitable means for marketing strategies.Keywords: brand image; purchase intention; skincare; brand